Capillary Hemangioma of Conjunctiva: A Rare Ocular Surface Growth - Chauhan, Anubhav (Pakistan Journal of Ophthalmology, 2017)
We report a case of a 17 year old mentally retarded male with a previous history of seizures who presented with a painless, progressively increasing mass in the right lateral conjunctival region. Histopathologic examination of the excised mass revealed it to be a capillary hemangioma. Keywords: Hemangioma, ocular, oral, excision